IMPACT OF ONLINE SOCIAL SPACES ON MENTAL HEALTH: ANALYZING THE RELATIONSHIP BETWEEN SOCIAL MEDIA ENGAGEMENT AND DEPRESSION AMONG BEIJING COLLEGE STUDENTS - Guanhui Li; Somsak Klaysung (Fonseca, Journal of Communication, 2024)
This research investigates the relationship between social media engagement and mental health among college students in Beijing, aiming to understand how various aspects of social media use influence emotional well-being. Key variables examined include social media information acceptance, the perceived role of social media, and the degree of dependence on these platforms. A quantitative approach was employed, involving a cross-sectional survey distributed to 400 college students out of which 320 were received. Data were collected using a structured questionnaire measuring social media engagement and mental health indicators. Statistical analysis, including correlation and regression techniques in SPSS, was utilized to explore relationships and identify significant predictors. The study revealed significant correlations between social media information acceptance, the perceived role of social media, and emotional outcomes such as anxiety and depression. Higher levels of social media dependence were associated with poorer mental health indicators. Gender, grade level, and current learning status were found to moderate these relationships. This study contributes to the literature by focusing on specific dimensions of social media use and their impact on mental health among Beijing college students. It provides nuanced insights into the complexities of social media engagement in an academic context and underscores the need for targeted interventions to promote healthy digital habits and support student well-being.